5PSQ-115 Near miss dispensing errors during working hours in inpatient dispensaries at a large UK teaching hospital. (24th March 2020) - Stewart-Kelcher, N; Elliott, L; Watson, L; Oborne, A; Vlassoff, A
Abstract : Background and importance: Errors in medication dispensing have potential to harm patients. 1 Up to 2.7% of dispensed medications include errors, although fewer 'near miss' data exist. 2 Near misses are 'a dispensing error detected by the checker before the patient receives the prescription'. 1 2 Audits defined a local near miss rate in 2013. This UK teaching hospital has two automated (acute, specialist) and one non-robotic (paediatric) dispensaries. Aim and objectives: To determine the frequency, time, staff group and harm potential of near misses. Material and methods: A group representing all stakeholders created a data collection tool based on the UK Centre for Pharmacy Postgraduate Education. 3 It recorded type, time and staff group for near misses in three dispensaries (paediatrics, adult acute and adult specialist). Data collection were piloted and then collected in September 2019 over 7 days. Two pharmacists independently rated the likelihood of harm. Results: Near misses totalled 190/8483 (2.24%) items: 1.10% (specialist), 1.41% (paediatrics) and 3.10% (acute) dispensaries (χ 2, p≤0.001). Most near misses (51, 26.8%) occurred between 5pm and 6pm. Assistant technical officers accounted for the highest proportion of near misses (16.8%, 32) followed by pharmacists (12.1%, 23), technicians (10%, 19), checking technicians (9.5%, 18), preregistration pharmacists (6.8%, 13) and trainee technicians (5.3%, 10): 71.1% (135) of near misses were graded likely to cause patient harm. Conclusion and relevance: Previous audits observed lower near miss rates than those found in 2019. Hurrying to complete work may account for the higher error rate between 5pm and 6 pm. Loss of three senior experienced pharmacists in 2015–2018 in the adult acute dispensary may have affected supervision of newly qualified pharmacists. The specialist dispensary implemented automation of drug selection in 2009, which may account for the 3.9% reduction in near misses. Reporting dispensing near misses may be too time consuming but regular audit may inform areas for improvement. References and/or acknowledgements: 1. James KL, et al. Incidence, type and causes of dispensing errors: A review of the literature. Int J Pharm Pract 2009;17:9–30. 2. James KL, et al. Unprevented or prevented dispensing incidents: which outcome to use in dispensing error research? Int J Pharm Pract 2011;19:36–50. 3. Centre for Pharmacy Postgraduate Education. Accuracy checking pharmacist technician programme. Available: https://www.cppe.ac.uk/career/acpt. Date accessed:02.09.19. No conflict of interest.